Experiences of Higher Education Students on the Autism Spectrum: Stories of Low Mood and High Resilience. Issue 4 (4th July 2022) - Fabri, Marc; Fenton, Grania; Andrews, Penny; Beaton, Mhairi
ABSTRACT: Increasing numbers of students on the autism spectrum enter higher education (HE), hoping to develop their skills and independence. However, many find it difficult to transition to and succeed in this environment, and the support provided by universities can be inconsistent as highlighted by a recent review. This study explores the personal experiences of 16 students with autism from four Western countries, focusing on successes and challenges. Using thematic analysis, four core themes were identified: choices and aspirations, being at university, support provisions, and specific recommendation . Anxiety, depression and mood difficulties were frequently reported. The importance of positive personal relationships, and the need for autism training and empathy amongst support professionals was highlighted. Further, there is a need for universities to provide joined up academic and social support and to implement reasonable adjustments in an inclusive way, thereby avoid stigmatising the student. Whilst negative experiences dominated, there were notable examples of good support practice and high levels of personal resilience and determination amongst the participants. To inform future practice, we conclude by offering a set of recommendations for educators, support professionals and for students on the autism spectrum.